FRI0533 Marked differences in occurrence of co-existing diseases at the time of diagnosis of various inflammatory rheumatic diseases. (23rd January 2014) - Jyrkkä, J.; Lönnroos, E.; Kautiainen, H.; Koponen, H.; Virta, L. J.; Pohjolainen, T.; Puolakka, K.
Abstract : Background: Co-existing diseases increase the burden caused by inflammatory rheumatic diseases (IRDs). Comorbidities may be associated with IRD-related factors or are independent. Objectives: To examine the occurrence of comorbidities among incident patients with several IRDs. Methods: Finland has a general sickness insurance covering the entire population. Patients with certain chronic diseases (e.g., chronic cardiac and pulmonary diseases, inflammatory bowel disease, IRDs, etc.) are entitled to special reimbursement of medications if their condition meets defined criteria. These patients are recorded in the national registry of the Social Insurance Institution. This registry was used to identify all incident cases of IRDs between 1 Jan 2000 and 31 Dec 2007. Data on their possible co-existing chronic diseases at the time of diagnosis were gathered from the same source. Results: During the 8-year period, 25 994 incident patients over 16 years of age with IRDs were identified. Of them, 14 878 (57%) had rheumatoid arthritis (RA) (63% RF-positive, 68% female), 3686 (44% female) spondylarthropathy (ICD 10-codes M45 and M46, SpA), 2942 (48% female) psoriatic arthritis (PsA), 802 (55% female) chronic reactive arthritis (ReA), and 3610 (65% female) chronic undifferentiated arthritis (UA). Table shows occurrence per cent of principal groups of co-existing diseases at the time of diagnosis of these rheumatic conditions. Conclusions: Occurrence of comorbidities differs markedly between various IRDs at the time of diagnosis. Disclosure of Interest: None Declared